Hyperemesis Gravidarum: Clinical Management and Nursing Care in Obstetric Practice-An Updated Review - Talaq, Sukinah Saeed Taki AL; Mona Mohammed Basirah (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Hyperemesis gravidarum (HG) is the most severe form of nausea and vomiting in pregnancy, marked by persistent vomiting, dehydration, weight loss exceeding 5% of prepregnancy weight, and significant metabolic disturbances. Unlike typical nausea and vomiting of pregnancy, HG follows a pathological course, often requiring hospitalization and posing risks of nutritional deficiencies, electrolyte imbalance, and complications such as Wernicke encephalopathy. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aims to provide an updated, comprehensive overview of the etiology, clinical features, evaluation, and management of hyperemesis gravidarum, with emphasis on evidence-based medical and nursing practices. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A narrative synthesis of current literature, clinical guidelines, and recent research was used to examine key aspects of HG, including hormonal, genetic, physiological, and psychosocial determinants, as well as clinical assessment tools, treatment strategies, and multidisciplinary care considerations. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Evidence indicates that HG is multifactorial, involving hormonal changes, genetic susceptibility, gastrointestinal adaptations, and neuroendocrine mechanisms. Diagnosis remains clinical and requires exclusion of other conditions. Effective management relies on a stepwise approach, starting with dietary and lifestyle modifications, progressing to antiemetic therapy, and escalating to enteral or parenteral nutrition when necessary. Psychological effects are significant, with increased rates of anxiety, depression, and reduced quality of life. The Pregnancy-Unique Quantification of Emesis and Nausea (PUQE) score provides objective assessment of severity. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Early recognition, structured treatment, and coordinated interdisciplinary care improve maternal recovery and fetal outcomes. Comprehensive management—including medical therapy, nutritional support, and psychological care—is essential for reducing complications and improving quality of life.